Are high-fit CSR programs always better? The effects of corporate reputation and CSR fit on stakeholder responses. (5th August 2019) - Kim, Yeonsoo; Ferguson, Mary Ann
Abstract : Purpose: The purpose of this paper is to examine how corporate reputation interacts with corporate social responsibility (CSR) fit and affects stakeholders' skeptical attribution (SA) of CSR motives, as well as their attitudes, supportive communication intent and purchase intent. This study proposes that a high-fit CSR program does not necessarily engender more favorable outcomes, nor does it stimulate SA. The study proposes the effects of CSR fit differ by corporate reputation. For bad-reputation companies, low-fit is anticipated to generate more desirable CSR outcomes than high-fit initiatives. Design/methodology/approach: Two experiments were conducted. The first experiment employed a randomized 2 (CSR fit: high fit vs low fit) × 2 (good reputation vs bad reputation) × 2 (Industry: food retailing and insurance) full factorial design to examine the suggested hypotheses. The second study employed a randomized 2 (CSR fit: high fit vs low fit) × 2 (good reputation vs bad reputation) full factorial design with consumer samples to replicate the conceptual relationships among variables in the first study. Findings: While reputation plays a dominant role in influencing stakeholders' CSR-related responses across both CSR fit situations, a SA partially mediates the relationship between reputation and stakeholder reactions. CSR fit interacts with reputation, and influences the partial mediation process through SA; under a bad reputation condition, low-fit CSR engenders less SA and results in better stakeholder reactions. A similar tendency was found with supportive communication intent and purchase intent. High-fit CSR initiatives by a negative reputation company engendered the weakest supportive intent and purchase intent. For a reputable company, across both CSR fits, respondents displayed generally very positive attitudes toward, greater intent to support, and intent to purchase from the company. Originality/value: The study findings provide useful and empirically supported logical explanations of why high-fit CSR programs sometimes cause backlash effects, despite the general consensus that such initiatives generate positive outcomes. This study offers an alternative and more relevant perspective to conceptualize the complexity of anticipating CSR outcomes.